Optical Imaging of the Motor Cortex Following Antidromic Activation of the Corticospinal Tract after Spinal Cord Injury - Lee, Kyung H.; Kim, Un J.; Park, Se W.; Park, Yong G.; Lee, Bae H. (Frontiers in Neuroscience, 2017)
Spinal cord injury (SCI) disrupts neuronal networks of ascending and descending tracts at the site of injury, leading to a loss of motor function. Restoration and new circuit formation are important components of the recovery process, which involves collateral sprouting of injured and uninjured fibers. The present study was conducted to determine cortical responses to antidromic stimulation of the corticospinal tracts, to compare changes in the reorganization of neural pathways within normal and spinal cord-injured rats, and to elucidate differences in spatiotemporal activity patterns of the natural progression and reorganization of neural pathways in normal and SCI animals using optical imaging. Optical signals were recorded from the motor cortex in response to electrical stimulation of the ventral horn of the L1 spinal cord. Motor evoked potentials (MEPs) were evaluated to demonstrate endogenous recovery of physiological functions after SCI. A significantly shorter N1 peak latency and broader activation in the MEP optical recordings were observed at 4 weeks after SCI, compared to 1 week after SCI. Spatiotemporal patterns in the cerebral cortex differed depending on functional recovery. In the present study, optical imaging was found to be useful in revealing functional changes and may reflect conditions of reorganization and/or changes in surviving neurons after SCI.